Hemorrhage control, infection prevention and application on anesthetics in exodontia of natal teeth - Šurdilović Dušan; Walid El Sayed; Ille Tatjana; Hamed Mohamed Said; Adtani Pooja Narain; Natarajan Prabhu Manickam D. (Medicinski fakultet i Klinika za stomatologiju, Niš, 2018)
Introduction: The teeth that appear at the time of birth are called Natal teeth. The exact cause of its appearance is unknown, but possible causes for this condition include infections, trauma, hormonal stimulation etc. There is a possibility to aspirate the tooth and difficulty with feeding. Case report: A one day old baby born with teeth in the lower jaw was referred to our dental department, Thumbay Hospital, Dubai, UAE. The crown structure was attached to the gums with grade 2 mobility (Millers classification). The shell like crown was removed with a periodontal curette and care was taken not to injure the underlying tooth. Vitamin K injection 1mg IM was given in the anterolateral thigh 2hours before the procedure. Conclusion: The appearance of natal teeth is a rare case however it is not uncommon in the newborns. Extraction as the first treatment choice should be performed as soon as possible considering all possible complications. Vitamin K administration is a mandatory step in the treatment.